¿Patriotismo o periodismo? - Rivas Troitiño, José Manuel (Estudios sobre el Mensaje Periodístico, 2002)
Following the terror attacks of Sept 11th, there exists a risk that the war against terrorism may have an inhibitory effect on the news media, a danger that the late Katherine Graham warned about. In that light, an «either/or» dilemma between patriotism, taken in the sense of an uncritical acceptance of whatever the official line may happen to be, and journalism, is considered as something fundamentally mistaken. Good journalism is unquestionably patriotic, insofar as it represents a counterweight and safeguard against abuses of power.
Keywords: Journalism; terrorism; patriotism